The Push and Pull Factors of Learners’ Participation in the Classroom Learning Process: The Case of Agona West District, Ghana - Oppong Frimpong, Samuel (Advances in Social Sciences Research Journal, 2022)
The push and pull factors of the classroom learning environment and learners’ participation has been an issue of concern to all stakeholders in education. This stems from the fact that there are factors of the classroom learning environment that can either enhance or impede a learner’s ability to actively participate and learn in the classroom. With the knowledge of this, two research questions were formulated to guide the collection of qualitative data in the form of interview and observation from 16 participants who were Early Childhood Education (ECE) teachers. The study employed case study design. The analysis of data and discussion of findings were done thematically being informed by the objectives of the study. The study revealed that seating arrangement, class size, instructional materials, nature of furniture and the classroom size and the relationship between teachers and their learners were among the factors that could either pull or push learners’ chances of actively participating in their classroom activities. Based on the findings, it is being recommended that the government of Ghana should expand infrastructure in the form of classrooms and provide developmentally appropriate furniture, particularly, at the kindergarten level to reduce the number of learners in a classroom to a size than can be conveniently managed by the teacher. The ECE teachers should create space in their classrooms to facilitate easy movement and subsequent learner participation. Learner centred pedagogy should be employed in lesson delivery at the ECE level and the teachers should also relate very well with their learners.